Pendidikan Bencana Dalam Perspektif Islam - Kusuma, Bukhori Brata; Muzani, Muzani (Jayapangus Press, 2024)
Misunderstanding of the teachings of Islam where people cannot distinguish between predestination and fatalistic attitudes, so that people ignore steps to reduce the risk of disaster. Predestiny attitude is an attitude that believes that every individual already has its own provisions, however, it can be changed through effort. While fatalistic is an attitude that believes that every individual already has provisions that cannot be changed. This research aims to provide a view on disaster education in an Islamic perspective and Islamic education in disaster risk reduction. Understanding the Islamic perspective on disasters is expected to be an effective approach to predestination and eliminating fatalistic attitudes. The research method used is the study of the library. Data collection is done by understanding and studying theories from various literatures related to this research. The findings from this literature review reveal that Islamic discourse sees disaster as a test from God. There is not a single verse in the Al-Qur'an and the hadith of the Prophet Muhammad that commands humans to surrender without any efforts to mitigate (fatalistic) but orders muslims to make efforts to mitigate themselves in disasters (predestination). The results of this research, namely fatalistic and predestini, are two concepts that often overlap, but have important differences in the meaning and concept of use. Fatalistic can cause apathy and predestination causes enthusiasm. Then this research offers three Islamic principles that can be used in disaster risk reduction, namely Al-Ilmu (knowledge), Ikhtiar (effort) and Tawakkul (trust in God) with these three concepts it is hoped that the Community can mitigate themselves and also those around them, so as to minimize the fall of victims in a disaster.